Human capital externalities with monopsonistic competition - Leo Kaas (Institute for the Study of Labor (IZA), 2008)
This paper provides a novel microeconomic foundation for pecuniary human capital externalities in a labor market model of monopsonistic competition. Multiple equilibria arise because of a strategic complementarity in investment decisions.
urn:nbn:de:101:1-20081014347
Keywords: D43; 330; Externalities; human capital; multiple equilibria; Bildungsinvestition; Externer Effekt; Arbeitsnachfrage; Humankapital; Monopolistischer Wettbewerb; Technologie; Qualifikation; Gleichgewicht; Theorie